A vertical grounding apparatus. - Gomes, Chandima (2010)

(untitled)
The present invention provides a vertical grounding apparatus to disperse current to earth which comprises a grounding electrode having a top end and a bottom end and a connecting means that connects the grounding electrode to ground cables, the connecting means comprising a pair of plates mounted to the top end and the bottom end of the grounding electrode. The outer wall of grounding electrode includes a plurality of projections that extend longitudinally between the top and bottom ends of the grounding electrode, thereby optimizing the grounding of electrical charges to earth by increasing the surface area of the grounding of electrical charges to earth by increasing the surface area of the grounding electrode. The vertical grounding electrode of the present invention is installed in a bore-hole via a concrete pit, where the space of the bore outside the outer-wall of the grounding electrode is filled with backfill material of a predetermined composition.